Accessing factor influencing customers to use food delivery services / Najihah Salehan - Salehan, Najihah (2020)
This research proposal related factor that influence consumer using food delivery. This purpose of this study to know factor that influence consumer using online food delivery. This study also can identify type of consumer likely using food delivery. Food delivery give facilities to customer get their food. However, the negative effect still can happen during delivery. Sometime customer must careful receive the other to make sure safe. To achieve this study, there a lot of journal, article, and other similar information can be reference to research this study. The reading information must relate this topic to get the right information.